Substitusi Tepung Kedelai (Glyine Max L.) Terhadap Sifat Organoleptik Soybeans Cookies - Ade Sareani; Luh Suranadi; Reni Sofiyatin (Jurnal Gizi Prima (Prime Nutrition Journal), 2019)
Background. Cookies are one of the biscuit snack products which are made from low-protein wheat flour so that there are high carbohydrates and fats. In this research, we will discuss cookies with the substitution of soy flour which is serelia with a high content of vegetable protein.Reseacrch Purpose. The purpose of this research was to determine the effect of soy flour substitution on the organoleptic properties of soybeans cookies which have low protein content into high protein cookies.Research Methods. Type of true experiment research in the laboratory with a one-factor complete randomized design (CRD) consisting of 5 treatment levels which obtained 15 experimental units. Organoleptic tests use hedonic methods with 5 numerical scales.Research Result. Based on the results of data analysis, there was no significant effect on the substitution of soy flour on organoleptic properties ( Color, smell, tate and texture) of soybeans cookies (p > 0,05). The hedonic test results favored by panelists are in treatment t1 and t2, t3, t4, t5 included in the category of approaching likes.Conclusion. The results of he statistical test showed that there was no significant effect on the substitution of soy flour on the organoleptic properties of soybeans cookies. This mean that there is no significant effect on the substitution of soy flour on organoleptic properties of soybeans cookies. So this research shows that the substitution of 15%-35% soy flour can be used in making soybeans cookies.